2023
DOI: 10.1186/s12967-023-03883-4
|View full text |Cite
|
Sign up to set email alerts
|

EREG is the core onco-immunological biomarker of cuproptosis and mediates the cross-talk between VEGF and CD99 signaling in glioblastoma

Abstract: Background Glioma is the most prevalent primary tumor of the central nervous system. Glioblastoma multiforme (GBM) is the most malignant form of glioma with an extremely poor prognosis. A novel, regulated cell death form of copper-induced cell death called “cuproptosis” provides a new prospect for cancer treatment by regulating cuproptosis. Methods Data from bulk RNA sequencing (RNA-seq) analysis (The Cancer Genome Atlas cohort and Chinese Glioma G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…39 EREG is the core onco-immunological biomarker of cuproptosis, and EREG knockdown can inhibit the proliferation, invasion, and migration of glioma cells. 40 To date, no relevant studies have been found on ADRM1 and IL18R1 in brain tumors. Mohan et al 41 reported that OSMR is upregulated in human brain tumor stem cells and correlated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 EREG is the core onco-immunological biomarker of cuproptosis, and EREG knockdown can inhibit the proliferation, invasion, and migration of glioma cells. 40 To date, no relevant studies have been found on ADRM1 and IL18R1 in brain tumors. Mohan et al 41 reported that OSMR is upregulated in human brain tumor stem cells and correlated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that ABI1 is involved in the regulation of GBM cell invasion 39 . EREG is the core onco‐immunological biomarker of cuproptosis, and EREG knockdown can inhibit the proliferation, invasion, and migration of glioma cells 40 . To date, no relevant studies have been found on ADRM1 and IL18R1 in brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic functions of EREG have been reported for various human cancers. Human recombinant EREG promotes cell proliferation in pancreatic [63] and bladder cancer [64] in a dose-dependent manner, whereas an EREG knockdown inhibits tumor growth in hepatocellular carcinoma [65], breast cancer [66], head and neck squamous cell carcinoma (HNSCC) [57], cervical cancer [54], glioma [67], and multiple myeloma [68]. Forced EREG expression enhances tumorigenicity in glioblastoma [58], salivary adenoid cystic carcinoma (SACC) [56], HNSCC [57], and esophageal cancer [59].…”
Section: Oncogenic Roles Of Ereg In Lung Cancermentioning
confidence: 99%
“…A recent study revealed that EREG is a core onco-immunological biomarker of cuproptosis [67], which is a molecular mechanism of regulated cell death [73]. Cuproptosis is induced by excessive copper, which binds to lipoylated dihydrolipoamide S-acetyltransferase (DLAT) [74].…”
Section: Oncogenic Roles Of Ereg In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation